PERANCANGAN SISTEM INFORMASI AKADEMIK MENGGUNAKAN METODE WATERFALL Studi Kasus: MADRASAHALIYAH AL-MANSYURIYAH KANZA MEKARJAYA TANGERANG - Muhammad Ali AS; Noer Azni Septiani (Jurnal Techno Nusa Mandiri, 2016)
Academic information system design aims to facilitate the students, teachers and the subject of Madrasah Aliyah Al-Mansyuriyah Kanza that previous long enough to know that information, here I make it easier for students, teachers and the subject of Madrasah Aliyah Al-Mansyuriyah Kanza with academic information system online, so it can be more efficient and effective. This thesis aims to build an online academic information system have as a web base. System design in making an academic website at Madrasah Aliyah Al-Mansyuriyah Kanza is developed using some software that Adobe Dreamweaver CS6, Xampp from Apache Web Server, PHP, and MySQL. Using the Adobe Dreamweaver CS6 then the website will work faster and easier. As for the tables used in making the web Academic Madrasah Aliyah Al-Mansyuriyah Kanza is a table of students, teachers table, value table, table schedule, log tables, table news, absences table. All of these tables will be used to accommodate the necessary data in the agencies website development Academic Madrasah Aliyah Al-Mansyuriyah Kanza.